Strengthening Social Studies Education in Society 5.0 - Nola Fibriyani (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2022)
Strengthening Social Studies Education in Society 5.0 Presented by Nola Fibriyani